2014
DOI: 10.1177/1043659614526253
|View full text |Cite
|
Sign up to set email alerts
|

Transcultural Self-Efficacy Perceptions of Baccalaureate Nursing Students

Abstract: Addressing the health care needs of a 21st-century nation that is experiencing increased diversity and disparity will require new models of educating future providers. The cultural competence and confidence model was the guiding framework in a study evaluating the influence of cultural educational offerings on the transcultural self-efficacy (TSE) perceptions in baccalaureate nursing students. The Transcultural Self-Efficacy Tool was used to measure perceived TSE in a pretest (N = 260), posttest (N = 236) stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(48 citation statements)
references
References 13 publications
5
35
0
7
Order By: Relevance
“…The Affective subscale (30 items) measures the degree of confidence in identifying values, attitudes, and beliefs concerning cultural awareness, acceptance, appreciation, recognition, and advocacy. Factor analysis of TSET scores has supported the three-dimensional structure (Chen, Wang, & Peng, 2015; Halter et al, 2015; Jeffreys & Dogan, 2012). …”
Section: Methodsmentioning
confidence: 94%
“…The Affective subscale (30 items) measures the degree of confidence in identifying values, attitudes, and beliefs concerning cultural awareness, acceptance, appreciation, recognition, and advocacy. Factor analysis of TSET scores has supported the three-dimensional structure (Chen, Wang, & Peng, 2015; Halter et al, 2015; Jeffreys & Dogan, 2012). …”
Section: Methodsmentioning
confidence: 94%
“…A variety of evidence-based educational strategies are used to enhance culturally competent nursing education. These include service-learning projects, objective structured clinical examinations (OSCE), case studies, role-play, self-reflection (Adams, 2012;Amerson, 2010;Rogers-Walker, 2014), domestic and foreign immersion experiences (Amerson, 2010;Czanderna, 2013;Larsen & Reif, 2011;Rogers-Walker, 2014;Schroeder, 2012), the use of high-fidelity manikins (Grossman et al, 2012;Halter, Grund, Fridline, See, Young, & Reece, 2014;Rutledge, Barham, Wiles, & Benjamin, 2008), the use of low-fidelity manikins (Phillips, Grant, Milligan, & Moss, 2012), and the use of SPs (Garrido et al, 2014;Ndiwane et al, 2014;Rutledge, Garzon, Scott, & Karlowicz, 2004).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Consideration of different learning styles of diverse student groups and determination of effective evidence-based teaching and learning interventions play an important role in helping students attain their educational goals. A current review of the literature revealed nurse educators implemented a variety teaching and learning strategies to enhance ADN, BSN, masters, and doctoral nursing students'cultural competence, such as: local or international service-learning projects (Adams, 2012;Amerson, 2010Amerson, , 2012Amerson & Livingston, 2014;Rogers-Walker, 2014;Schmidt, 2012), international immersion experiences (Czanderna, 2013), domestic immersion experiences (Larsen & Reif, 2011;Schroeder, 2012), global web-conferencing (Spalla, 2012), integration of cultural competence objectives in the curriculum (Creech et al, 2017;Jeffreys & Dogan, 2012;Jeffreys & Smodlaka, 1996;1998;1999a;1999b;Singleton, 2017), case studies, gaming, role play, face-to-face classrooms, and hybrid and online courses (Adams & Nevel, 2016a;Curtis, Bultas, & Green, 2011Halter et al, 2014), Cultural Discovery (Jeffreys & O'Donnell, 1997;Jeffreys & Dogan, 2012;Jeffreys, O'Donnell, & Xiao, 2010, 2016a, innovative field trip experience (Jeffreys, Bertone, Douglas, Li, & Newman, 2016a), flipped cultural simulation (McArthur, Mixer, & Fancher, 2016a), the use of low-and high-fidelity patient simulation (Garrido et al, 2014;Grossman et al, 2012;Halter et al, 2014;Odreman, 2016;Phillips et al, 2012;Rutledge et al, 2008), virtual simulation experience (VSE)…”
Section: Strategiesmentioning
confidence: 99%
See 2 more Smart Citations